PENGARUH PENERAPAN MODUL DALAM PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SEMESTER 1 DI SMAN 1 KUBUNG KABUPATEN SOLOK - Rizki Fernanda; Ernmaniati Ramli; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2015)
This study is based on facts on the ground in general, one of which students are less develop problem solving skills and develop science process skills in physics. The purpose of this study was to determine the effect of the application modules in discovery learning physics learning on learning outcomes of students of class X of SMAN 1 Kubung Kabupaten Solok. Moreover, it can increase the motivation and creativity of students in learning and apply it in everyday life. This study is a kind of quasi-experimental design with randomized control group only design. Population is a class X of SMAN 1 Kubung Kabupaten Solok registered in the 1st 2014/2015 academic year. Sampling used random cluster sampling technique. Samples are Xipa2 class as a class control and Xipa1 class as a class experiment. The research data is the result of learning on aspects of knowledge, attitudes and skills. The research instrument was the final test, observation and performance assessment sheet.Based on data analysis of learning outcomes on average in the aspect of knowledge is 79.23 to 74.67 for the experimental class and control class. In the aspect of attitude is 82.17 to 78.11 for the experimental class and control class. Furthermore, in the aspect of the skills acquired 76.93 to 74.11 for the experimental class and control class. After the t test for two sample groups on aspects of knowledge gained t = 1.86 is greater than table = 1.67. In the aspect of attitude obtained t = 3.15 is greater than 1.67 and table =. in the aspect of skills obtained t = 1.68 is greater than table = 1.67. Conclusion of the study is the hypothesis that there is a significant impact on the use of the module in the learning discovery learning on learning outcomes of physics in the first half of the tenth grade high school SMAN 1 Kubung Kabupaten Solok can be accepted on the real level of 0.05